Toward the Theory of Traffic Flow Organisation - Ivan Dadić; Goran Kos; Emil Gašparić (Promet - Traffic&Transportation, 1970)
Every traffic network can be reorganised, i.e. the trafficflows may be redirected and guided along other routes. Mathematicalcalculation of the number of intersecting points, mergingand diverging of traffic can determine the cu'ent volume ofconflicting traffic flows in the network. The aim of redirectingtraffic flows is to obtain lower intensity of intersecting flows, indicatingat the same time bel/er organisation of traffic flows.The work presents a model of traffic flow intersections on anisolated road section. It also provides mathematical formulasfor calculating the number of collision points for the same anda different number of entrances and exits (nodes). The problemis further developed for the case which searches for the numberof conflicting points of traffic flows with two-way traffic. Amathematical formula has been found for the same number ofentries and exits (nodes, or sources and sinks) of traffic flows.